THE METAMORPHOSIS OF NORMATIVE REVIEW IN THE CONSTITUTIONS OF TURKEY - Çelebi, Özge (International Scientific Journal Vision, 2024)
The subject of this study is the emergence and development of norm review in Turkey. Our study covers the process of transition from political norm review to legal norm review in Turkey, the constitutional arrangements in this process, and the changes made by the derivative constituent power. In this context, it analyses and evaluates the norms that are subject to constitutional review in Turkey, the norms that are prohibited from review, the types of norm review, the persons who apply to the Constitutional Court for norm review, and the duration of the review. Our study first presents constitutional models in general and then explains the historical reasons for Turkey's adoption of these constitutional models. Then, in the constitutional history of Ottoman Turkey, from the first written constitution to the current constitution, the development of both political and legal review of the constitutionality of norms in all texts is explained. Subsequently, the types of norm review in the constitutional judiciary established by the 1961 Constitution are analysed in detail in terms of the applicants, the norms subject to review and the duration of the review. The innovations introduced by the 1971 amendments to the 1961 Constitution are analysed in terms of the rule of law and the results of the comparison with the first version of the Constitution. Finally, the amendments to the 1982 Constitution, which is currently in force, are presented and evaluated, first in their original form and then by the derived constituent power. Finally, all the constitutional amendments have been systematically analysed, the resulting developments examined and solutions proposed for various improvements.